Role of Social Media Marketing on Consumer Buying Behavior on Alcoholic Product inside Kathmandu Valley - Yeak Narayan Sharma (Interdisciplinary Journal of Management and Social Sciences, 2022)
This study investigates the effect of different social media marketing in consumer buying behavior on liquor products inside the Kathmandu Valley. Consumers’ behavior is the dependent variable, and perceived value, quality service, usefulness, awareness, word of mouth, entertainment, and credibility are the independent variable. The primary data source is a respondent’s opinion regarding consumer buying behavior through social media marketing. There are 101 respondents incorporated to reach the purpose of the study. The study followed a structured questionnaire and used a descriptive model to identify the relationship between important factors with consumer behavior be in Kathmandu valley.This study shows the perceived value of service of quality is positively related to consumer buying behavior and indicates that higher the perceived value would positive value of consumer buying behavior. Similarly, there is a positive relationship between perceived usefulness for consumer buying behavior, indicating that a higher perceived value of usefulness increases consumer buying behavior. The result also shows a positive correlation between word of mouth and consumer behavior. Itindicates that the higher the positive word of mouth concern would increase consumer buying behavior.Also, entertainment has a positive relation to brand loyalty; indicate that take higher the result of entertainment; the higher would be consumer buying behavior. There is a positive relationship between credibility and consumer buying behavior; it indicates that positive credibility increases consumer buying behavior. The descriptive static is used to measure the result that the higher mean value for perceived service quality, usefulness, word of mouth, credibility, entertainment, and other factors affects consumer buying behavior.